Poly(I:C) model of schizophrenia in rats induces sex-dependent functional brain changes detected by MRI that are not reversed by aripiprazole treatment - Drazanova, Eva; Ruda-Kucerova, Jana; Kratka, Lucie; Horska, Katerina; Demlova, Regina; Starcuk, Zenon; Kasparek, Tomas (Brain research bulletin, 2018)
BACKGROUND AND PURPOSE: One of the hallmarks of schizophrenia is altered brain structure, potentially due to antipsychotic treatment, the disorder itself or both. It was proposed that functional changes may precede the structural ones. In order to understand and potentially prevent this unwanted process, brain function assessment should be validated as a diagnostic tool. METHODS: We used Arterial Spin Labelling MRI technique for the evaluation of brain perfusion in several brain regions in a neurodevelopmental poly(I:C) model of schizophrenia (8mg/kg on a gestational day 15) in rats taking into account sex-dependent effects and chronic treatment with aripiprazole (30days), an atypical antipsychotic acting as a partial agonist on dopaminergic receptors. RESULTS: We found the sex of the animal to have a highly significant effect in all regions of interest, with females showing lower blood perfusion than males. However, both males and females treated prenatally with poly(I:C) showed enlargement of the lateral ventricles. Furthermore, we detected increased perfusion in the circle of Willis, hippocampus, and sensorimotor cortex, which was not influenced by chronic atypical antipsychotic aripiprazole treatment in male poly(I:C) rats. CONCLUSION: We hypothesize that perfusion alterations may be caused by the hyperdopaminergic activity in the poly(I:C) model, and the absence of aripiprazole effect on perfusion in brain regions related to schizophrenia may be due to its partial agonistic mechanism.
Keywords: Random Allocation; MRI; Schizophrenia; těhotenství; mozkový krevní oběh; Disease Models, Animal; Rats, Wistar; mužské pohlaví; mozek; Antipsychotic Agents; poly I-C; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Sex; modely nemocí na zvířatech; ženské pohlaví; zvířata; Pregnancy; Sex Characteristics; zpožděný efekt prenatální expozice; náhodné rozdělení; Aripiprazole; Poly I-C; schizofrenie; antipsychotika; Cerebrovascular Circulation; aripiprazol; Wistar rats; Arterial Spin Labelling; potkani Wistar; pohlavní dimorfismus; Female; Prenatal Exposure Delayed Effects; Male; Animals